Isolation and Identification of Potential Probiotic White Snapper (Lates calcarifer) - Rahmad Lingga (El-Hayah, 2022)
Lactic acid bacteria are one of the bacteria found in the digestive tract of white snapper (Lates calcarifer) which can potentially be probiotics and have the ability to produce antimicrobial metabolism that is able to suppress pathogenic bacteria. This study aims to isolate and identify lactic acid bacteria from the intestines of white snapper This research uses qualitative and quantitative methods. This study obtained 3 isolates that showed characterization of lactic acid bacteria. The results of the study showed the characteristics of lactic acid bacteria identified as bacteria of the genus Lactobacillus which are gram-positive bacteria that have the potential to be probiotics.